Synthesis and crystal structures of a poliaza receptor macroligand: 1,3-bis(2-nitrobenzylideneamino)propan-2-OL - Elizondo Martínez, Perla; Pérez Rodríguez, Nancy; Rodríguez de Barbarín, Cecilia; López Cortina, Susana; Rodríguez de Luna, Sara Luisa (2010)
The asymmetric unit 01 the title compound C"H"N,O" centains one molecule 01 the cempound (L3) (1 ,3-bis(2-nitrobenzylideneamino)propan-2-o1). The molecule shows a chiral e atom but the absolute structure was not possible lo be detemnined by X-ray diffraction. The molecule shows intermolecular hydrogen bonding involving !he hydroxy group and an imine nitrogen atom of a symmetry related molecule. The molecular distribution shows weak interactions belween oxygen aloms ofthe nitro groups and Iwo different C-H groups 01 benzene rings. The extended weak H bond lomnation, using the NO, groups, probably gives a more stable crystal structure. The molecule represents a precursor of a polyaza macrocylic ligands.